Pengaruh Lingkungan Sekolah Terhadap Pendidikan Karakter Siswa Kelas V Di SDN Pekapuran Raya 5 Kota Banjarmasin - Rizkina, Amalia (Yayasan Pendidikan Internasional Bengkulu, 2023)
This study aims to determine the effect of school environment on character education of fifth grade students at SDN Pekapuran Raya 5 Banjarmasin City. The research method used in this research is a quantitative approach with experimental research type. The data collection tools in this research are questionnaires and documentation. Data analysis used simple linear regression. The results of this study indicate that the results of the calculation test, obtained the value of the regression equation is Y = 2.688 + 1.917X. based on the results of the calculation obtained the value of t count (tb) of tcount = 2.63> t table = 1.69 or tcount = 2.63> t table = 2.45 then Ho is rejected or Ha is accepted. This means that there is an influence between the school environment on student character education at SDN Pekapuran Raya 5 Banjarmasin City.